A Value-Based Approach to AI Ethics: Accountability, Transparency, Explainability, and Usability - Iyer, Vish; Manshad, Moe; Brannon, Daniel (Mercados y Negocios, 2025)
As artificial intelligence (AI) becomes increasingly prevalent, ensuring its ethical development and deployment is paramount. This paper proposes a value-based approach to AI ethics, focusing on four key principles: accountability, transparency, explainability, and usability. By examining these principles, providing real-world examples, and discussing implementation challenges, we contribute to the ongoing discourse on responsible AI development and offer practical insights for stakeholders across various industries.